Effect of growth stage on the efficacy of postemergence herbicides on four weed species of direct-seeded rice - Chauhan, Bhagirath Singh; Abugho, Seth Bernard (Hindawi Limited, 2012)
The efficacy of bispyribac-sodium, fenoxaprop + ethoxysulfuron, and penoxsulam + cyhalofop was evaluated against barnyardgrass, Chinese sprangletop, junglerice, and southern crabgrass when applied at four-, six-, and eight-leaf stages. When applied at the four-leaf stage, bispyribac-sodium provided greater than 97% control of barnyardgrass, junglerice, and southern crabgrass; however, it was slightly weak (74% control) on Chinese sprangletop. Irrespective of the weed species, fenoxaprop + ethoxysulfuron provided greater than 97% control when applied at the four-leaf stage. At the same leaf stage, penoxsulam + cyhalofop controlled 89 to 100% barnyardgrass, Chinese sprangletop, and junglerice and only 54% of southern crabgrass. The efficacy of herbicides was reduced when applied at the eight-leaf stage of the weeds; however, at this stage, fenoxaprop + ethoxysulfuron was effective in controlling 99% of Chinese sprangletop. The results demonstrate the importance of early herbicide application in controlling the weeds. The study identified that at the six-leaf stage of the weeds, fenoxaprop + ethoxysulfuron can effectively control Chinese sprangletop and southern crabgrass, penoxsulam + cyhalofop can effectively control Chinese sprangletop, and bispyribac-sodium can effectively control junglerice.